Implementasi Manajemen Pelayanan Sirkulasi Perpustakaan SMPN 6 Rejang Lebong - Murniyanto Murniyanto (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Borrowing and returning library books is a process of circulation service activities. This research is motivated by the fact that library circulation service management is very important in order to improve the quality of existing services, where officers must understand the problems in the implementation of circulation in the library. The purpose of this study was to analyze the implementation of circulation service management in the Rejang Lebong 6 Junior High School Library. The type of approach used in this research is a qualitative approach. Data were collected using observation, interview, and documentation techniques. The results showed that the implementation of circulation service management at the Rejang Lebong 6 Junior High School Library has not run optimally, this is indicated by the many problems in circulation services. There are still officers who do not understand how to use the library so that the service has not been running optimally. On the other hand, library infrastructure is still lacking, so that it has an impact on library management, which will have implications for the learning process in schools.